Keberadaan Masjid Al-Solihin Kayu Agung Sebagai Pusat Sosial, Edukasi, dan Ekonomi Masyarakat - Aurelia Solihatun Hasanah; Atia Subaida Handeza; Widya Ayu; Anisa Agustina Sari; Hudaidah Hudaidah (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2026)
Solihin Mosque in Kayuagung is a vital civilization symbol and a historical witness to the local struggle against colonialism along the OKI River. Despite its significance, academic research on its physical and socio-educational transformations remains scarce compared to mosques in central Palembang. This study aims to elucidate the mosque’s architectural evolution and analyze its role in strengthening contemporary social and religious education. Using a descriptive-qualitative method and a historical approach, the research reveals that the mosque has transitioned from a traditional unglen (ironwood) structure to a modern domed building. Functionally, it remains a community hub through professional management, including the Al-Qur'an Education Center (TPA), the Mosque Youth Association (IRMA), and local economic stimulation through religious tourism near ulamas' graves in Sidakersa. These findings demonstrate that modernization need not erase historical identity if supported by flexible management. This research offers strategic insights into preserving local historical narratives to maintain social cohesion and intergenerational understanding of Islamic heritage in the Ogan Komering Ilir region.